2011
DOI: 10.4161/epi.6.1.13390
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of telomeric regions during the generation of human induced pluripotent stem cells and subsequent differentiation into fibroblast-like derivatives

Abstract: Human induced pluripotent stem (hiPS) cells provide therapeutic promises, as well as a potent in vitro model for studying biological processes which take place during human embryonic development and subsequent differentiation in normal and disease states. The epigenetic characteristics of iPS cells are reprogrammed to the embryonic state at which they acquire pluripotency. In addition, telomeres in hiPS cell must elongate sufficiently to provide the necessary replicative potential. Recent studies have demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 65 publications
2
75
0
2
Order By: Relevance
“…MYC and KLF-4, 2 of the transcription factors commonly used to derive iPSCs and endogenously upregulated following reprogramming, directly or indirectly induce TERT expression (30,34). Reprogramming is associated with de novo changes in methylation of subtelomeric chromosomal regions and elevation of telomeric-repeat-containing RNA (TERRA) expression, indicating that significant changes in the architecture and function of telomeric and subtelomeric structures take place during this process (19).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…MYC and KLF-4, 2 of the transcription factors commonly used to derive iPSCs and endogenously upregulated following reprogramming, directly or indirectly induce TERT expression (30,34). Reprogramming is associated with de novo changes in methylation of subtelomeric chromosomal regions and elevation of telomeric-repeat-containing RNA (TERRA) expression, indicating that significant changes in the architecture and function of telomeric and subtelomeric structures take place during this process (19).…”
Section: Figurementioning
confidence: 99%
“…The induction of telomerase expression and resultant telomere elongation occur following reprogramming of somatic cells to pluripotency in both murine (18) and human (19) iPSCs. MYC and KLF-4, 2 of the transcription factors commonly used to derive iPSCs and endogenously upregulated following reprogramming, directly or indirectly induce TERT expression (30,34).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that iPSCs could not be generated from somatic cells from late generations (G3) of telomerase-null mice, possibly due to the high degrees of genomic instability as a result of telomere fusions, and that reintroduction of telomerase could restore the efficiency of generating iPSCs [50] . Interestingly, iPSCs derived from normal human and mouse cells show progressive telomere elongation with passaging in cultures, indicating that telomere elongation can occur postprogramming [50][51][52][53] . Studies have also shown that telomerase enzymatic activity is significantly activated upon iPS manipulation [38][39][40]50,52,54] as a result of upregulated expression of the TERT protein and TERC RNA, as well as of the associated protein dyskerin [52,54] .…”
Section: Effects Of Cloning On Telomeres and Telomerase Of Normal Cellsmentioning
confidence: 99%
“…During the telomeric crisis towards immortalization a series of marked changes should occur accompanied by the reorganization of chromosomes. These changes may include epigenetic ones around telomeric regions as observed during the generation of human pluripotent stem cells (17).…”
Section: Role Of Wrn Gene In Breakage-fusion-bridge Cycle At Telomerimentioning
confidence: 99%